2014
DOI: 10.1016/j.bmcl.2014.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotides conjugated with short chemically defined polyethylene glycol chains are efficient antisense agents

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 18 publications
0
19
0
1
Order By: Relevance
“…Depending on the size of the attached ligand, renal elimination is a threat. This can be avoided by increasing the molecular size, for example by PEGylation [178][179][180]. In contrast to particle systems, bioconjugates are more readily distributed into organs, since they are not depending on endothelial fenestrations.…”
Section: Bioconjugates For Targeted Deliverymentioning
confidence: 96%
“…Depending on the size of the attached ligand, renal elimination is a threat. This can be avoided by increasing the molecular size, for example by PEGylation [178][179][180]. In contrast to particle systems, bioconjugates are more readily distributed into organs, since they are not depending on endothelial fenestrations.…”
Section: Bioconjugates For Targeted Deliverymentioning
confidence: 96%
“…As demonstrated for siRNAs, short PEG 12 chains do not reduce the efficiency of antisense oligonucleotides [61]. Superior efficacy was found after lipoplex mediated application of both wild-type and phosphorothioate backbone modified antisense oligonucleotides in 100 nM concentrations targeted at bcl-2 in a cell culture reporter assay.…”
Section: Key Termmentioning
confidence: 94%
“…Recent reports indicate that the use of slightly longer PEG chains positively influence cellular uptake, but only together with a transfection enhancing system [61]. Attachment at the 2´-position would enable a sequence-wide distribution of PEG substituents, and could potentially increase membrane permeability of antisense oligonucleotides, the precise challenge that currently limits a wider thera-peutic use.…”
Section: Review Winklermentioning
confidence: 99%
“…In contrast, Park et al have PEGylated double-stranded siRNA at all possible termini (5′ sense/antisense or 3′ sense/antisense), and discovered that gene silencing activity was not affected by the conjugation site [80]. Similarly, Winkler et al have also reported nearly identical knockdown efficacies using two PEGylated antisense strands at either 5′ or 3′ [81]. Internal positions (often via 2′-O) are also used.…”
Section: Pegylation Of Ons Using Linear or Slightly Branched Pegmentioning
confidence: 99%